1980
DOI: 10.1073/pnas.77.2.1015
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of membrane internalization and recycling during pinocytosis in Dictyostelium discoideum.

Abstract: Internalization and recycling of plasma membrane during pinocytosis in Dictyostelium discoideum was analyzed quantitatively. A labeling technique was used by which [3Hlgalactose could be enzymaticallybound to and released from the plasma membrane. Label internalized with the plasma membrane was no longer accessible to enzymatic release and could therefore be distinguished quantitatively from label remaining on the cell surface. Internalization of labeled membrane components was measured as a function of pinocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 26 publications
3
59
0
Order By: Relevance
“…Internalisation of macromolecules via cell surface receptors has not been observed in D. discoideum. In addition, it was calculated by comparing internalised volume and membrane surface that the average diameter of primary pinosomes is 0.6 IJm (Thilo and Vogel 1980). Extensive observation of living D. discoideum cells with confocal microscopy further showed that newly formed pinosomes average 1.6 IJm in diameter and that the frequency of macropinosome formation may account for nearly all fluid-phase uptake (Hacker et al 1997).…”
Section: Uptake Mechanismsmentioning
confidence: 99%
“…Internalisation of macromolecules via cell surface receptors has not been observed in D. discoideum. In addition, it was calculated by comparing internalised volume and membrane surface that the average diameter of primary pinosomes is 0.6 IJm (Thilo and Vogel 1980). Extensive observation of living D. discoideum cells with confocal microscopy further showed that newly formed pinosomes average 1.6 IJm in diameter and that the frequency of macropinosome formation may account for nearly all fluid-phase uptake (Hacker et al 1997).…”
Section: Uptake Mechanismsmentioning
confidence: 99%
“…A model, taking into consideration these and other data on Acanthamoeba, is proposed to account for the observed membrane shifts . The data suggest that the vacuolar (digestive) system of Acanthamoeba is central to cellular control of endocytosis and membrane recycling.Evidence from several different kinds of studies suggests that the bulk of cell surface membrane in free-living endocytic cells is in a reversible equilibrium with cytoplasmic vacuolar system (4,6,12,(15)(16)(17)(18). The rate of cell surface turnover in these cells is very high, on the order of minutes (4,17,18) .…”
mentioning
confidence: 96%
“…The rate of cell surface turnover in these cells is very high, on the order of minutes (4,17,18) . The dynamics of the membrane flow and the cytoplasmic membrane relationships are complex so that a complete definition of the pathway of membrane flow in a single system is not yet available.…”
mentioning
confidence: 99%
“…Pinocytotic activity was determined using FITC-dextran and following procedures described (13) . Cells, suspended at a density of 5 x 106 cells/ml in growth medium, or 1 x 10' cells/ml in starvation medium were mixed with FITCdextran at a final concentration of 1 mg/ml.…”
Section: Pinocytosis Assaymentioning
confidence: 99%